Chattering analysis on finite/fixed-time consensus of multi-agent systems. (2nd January 2022) - Wu, Jie; Wang, Xiaofeng; Ma, Ruru; Pan, Xiaohong; Zhao, Li
ABSTRACT: Our investigation concerns the chattering problem existing in conventional finite/fixed-time control strategies. For resolving the chattering problem resulting from the signum function, this paper implements novel protocols to reach chattering-free consensus of multi-agent systems(MAS) within a finite/fixed time. The relationship between the chattering-free consensus protocol and the traditional finite/fixed-time control schemes containing the signum function is uncovered for the first time. Moreover, we find that the stochastic noise is another factor that causes chattering in MAS. In the light of Lyapunov methods, the criteria are deduced to ensure the realization of stochastic consensus of MAS in a finite/fixed time. At last, the effectiveness of presented consensus protocols is validated via several simulations.